ISOLATED UNILATERAL PTOSIS DUE TO JUVENILE OCULAR MYASTHENIA GRAVIS, CASE REPORT - Pramanto, Adji; Sutyawan, Eka (Majalah Oftalmologi Indonesia, 2025)
Introduction: Ocular myasthenia gravis in children is an uncommon autoimmune condition impacting the neuromuscular junction. Typical manifestations include weakness in the levator palpebrae, orbicularis oculi, or extraocular muscles, leading to symptoms such as ptosis and binocular diplopia.   Case Report: a 5-year-old girl was brought in with the primary concern of her right eyelid drooping for the last 11 days. The weakness of the eyelid is more pronounced during daytime and nighttime but improves upon waking up in the morning. The patient did not experience difficulties in speaking, swallowing, or breathing. There was no extremity weakness. Ophthalmologic examination reveals orthophoric eye position without restriction of eye movement. The patient exhibited drooping of the right eyelid. Repetitive Nerve Stimulation (RNS) confirmed the presence of a lesion at the neuromuscular junction. Consequently, the diagnosis was made of myasthenia gravis causing the right eye ptosis. Seven months after beginning treatment with oral pyridostigmine, there was a noticeable improvement in the patient's condition during a follow-up examination.   Discussion: Juvenile ocular myasthenia gravis, can present with isolated unilateral ptosis. Diagnosis of mechanical/congenital ptosis, external ophthalmoplegia, and Horner syndrome has ptosis as a manifestation was ruled out.   Conclusion: The diagnosis and initial management of juvenile ocular myasthenia gravis play a crucial role in preventing disease progression. First-line therapy with oral pyridostigmine is safe and effective. The prognosis for ocular myasthenia gravis in prepubertal patients is generally favorable.